Penerapan Teknik Pengelolaan Diri Untuk Meningkatkan Kemampuan Pengelolaan Waktu Pada Mahasiswa (Indonesian Journal of Learning Education and Counseling, 2020)
The purpose of this study is to determine the effect of self-management techniques to improve time management skills. The data collection technique in this study uses a questionnaire with a research sample of 30 students from all students of STKIP Andi Matappa with a population of 120. student people. The type of research used in this research is experimental research with a one group pretest-posttest desaign research design. The results showed that the level of student time management before being given treatment in the form of self-management techniques was in the low category. Furthermore, the level of student time management after being given treatment in the form of self-management techniques is in the high category. In addition, based on the results of the research hypothesis test, it can be concluded that there is an effect of the application of self-management techniques on the time management of students.